The importance of teaching aids and their impact on the teaching of the Arabic Language/أهمية الوسائل التعليمية وأثرها في تعليم اللغة العربية - Umar Manshur (Nurul Jadid University, 2018)
Media have important role in improving the linguistic competence of students. Hence, well-prepared media will influence good result of learning and simplify Arabic material for students. The variety of use of instructional media should be fit to the objectives of learning, because the goal of listening is different from reading or other skills. So, each learning objective of the four skills require particular media that can support the success of learning process in accordance with characteristics of each.إن الوسائل التعليمية لها دور هام في ترقية مهارة لغة الطلبة العربية. فإعداد الوسائل التعليمية يساعد الطلبة على فهم المواد الدراسية بسهولة ويسر. واستخدام الوسائل التعليمية أن تلائم أهداف التعليم المناسبة لكل من مهارات اللغة الأربع حيث اختلفت مهارة الاستماع عن مهارات اللغة الأخرى كمهارة القراءة. لذا، فإن تعليم مهارات اللغة الأربع في حاجة ماسة إلى الوسيلة التعليمية المناسبة كي تتحقق العملية التعليمية بنجاح وفعال مع مراعاة خصائص كل من مهارة لغوية مذكورة.